Pyrolysis of biomass mixture of coconut fiber and rice husk waste with polypropylene plastic - Bagas Cahya Mardikatama; Danar Susilo Wijayanto; Taufik Wisnu Saputra (International Journal of Advances in Applied Sciences, 2024)
This research aims to evaluate the effect of the composition ratio of oil from coconut fiber waste biomass and rice husks as well as polypropylene (PP) plastic which is not optimally utilized and can be used as an alternative fuel processed through the pyrolysis process. This research was conducted by mixing biomass of coconut fiber and rice husk with PP plastic in the form of refuse-derived fuel (RDF)-3 with compositional variations of 100:0%, 75:25%, 50:50%, 75:25%, and 0:100% for 60 minutes. The pyrolysis product in the form of oil was then distilled to separate the compounds contained in it and produce pure oil. Next, quantity (volume of pyrolysis oil and distilled oil) and quality (yield, density, viscosity, visual, and color) tests were carried out. The results of the study showed that there is an influence of the variation in the composition ratio of the mixture of biomass of coconut fiber and rice husk and PP plastic on its quantity and quality. The highest quantity was obtained from the 100% PP ratio and the best quality was obtained from the 100% PP ratio, which leads to the specifications of solar fuel oil.